Axillary Artery Aneurysm: A Rare Case Report - Tüzün, Hasan; Arslan, Caner; Deşer, Serkan Burç; Denli, Şeyma (Cerrahpaşa Medical Journal, 2020)
Upper extremity arterial aneurysms are uncommon lesions and the most common false aneurysms. True upper extremity aneurysms of the axillary artery are most commonly caused by atherosclerosis; blunt trauma; or arteriosclerotic, congenital, and metabolic disorders, as well as with Kawasaki’s syndrome, Buerger’s disease, Kaposi’s sarcoma, or adventitial cystic disease. The mechanism of aneurysm formation is considered as the compression of the arterial wall resulting in the contusion of the arterial media with subsequent weakness of the wall and fusiform dilatation. A 45-year-old male patient presented with a prediagnosis of axillary artery pain in the left armpit and a 6-cm aneurysmatic dilatation of the left axillary artery. Herein, we present the surgical treatment of a rare isolated giant axillary artery aneurysm. Cite this article as: Tüzün H, Arslan C, Deşer SB, Denli Ş. Axillary Artery Aneurysm: A Rare Case Report. Cerrahpasa Med J 2020; 44(1): 54-56.